2015
DOI: 10.1111/mec.13192
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and morphological differentiation in Populus nigra L.: isolation by colonization or isolation by adaptation?

Abstract: Identifying processes underlying the genetic and morphological differences among populations is a central question of evolutionary biology. Forest trees typically contain high levels of neutral genetic variation, and genetic differences are often correlated with geographic distance between populations [isolation by distance (IBD)] or are due to historic vicariance events [isolation by colonization (IBC)]. In contrast, morphological differences are largely due to local adaptation. Here, we examined genetic (mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
51
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 96 publications
(176 reference statements)
11
51
0
Order By: Relevance
“…These patterns confirm that multiple evolutionary processes influence the morphological diversity and structure of the populations (DeWoody et al 2015). In general, two distinct morphotypes were found: small-leaf in the mountainous Alpine-Dinaric region, and large-leaf in the continental region.…”
Section: Conclusion Zaključcisupporting
confidence: 69%
See 2 more Smart Citations
“…These patterns confirm that multiple evolutionary processes influence the morphological diversity and structure of the populations (DeWoody et al 2015). In general, two distinct morphotypes were found: small-leaf in the mountainous Alpine-Dinaric region, and large-leaf in the continental region.…”
Section: Conclusion Zaključcisupporting
confidence: 69%
“…The isolation by distance assumes that phenotypic differentiation between populations increases with increasing geographic distance because of limited pollen and seed dispersal (Wright 1943(Wright , 1946Orsini et al 2013). On the other hand, gene flow among ecologically divergent habitats is reduced because of reduced success of the establishment of immigrants from different environments, as a result of local genetic adaptation (Nosil and Crespi 2004;Noisl et al 2005Noisl et al , 2008Noisl et al , 2009Orsini et al 2013;DeWoody et al 2015). However, we cannot exclude the possibility that adaptive differentiation and historical migration processes acted in combination to produce the observed pattern of morphological variation in the studied populations (Temunović et al 2012;DeWoody et al 2015).…”
Section: Raspravamentioning
confidence: 99%
See 1 more Smart Citation
“…These spatial processes are not mutually exclusive and can act together to decrease gene flow among ecologically divergent populations (DeWoody et al., 2015; Papadopulos et al., 2014). Therefore, disentangling their relative contributions is very challenging, and attributing patterns of genetic variation to a single factor can be an oversimplification of the processes involved.…”
Section: Discussionmentioning
confidence: 99%
“…Different studies showed that spatial separation of Populus spp. populations is governed by historical processes, mainly by events in the Pleistocene and Holocene (Keller et al, 2010;Macaya-Sanz et al, 2012;Dewoody et al, 2015;Meirmans et al, 2017;Fan et al, 2018). Therefore, the variability of P. laurifolia population structure in the Tom River basin is the subject for a further extended research.…”
Section: Discussionmentioning
confidence: 99%